PERSEPSI PUBLIK LINGKAR INDUSTRI PERTAMBANGAN TERHADAP KEBERADAAN TENAGA KERJA ASING (Studi Kasus PT. Virtue Dragon Nickel Industri, Kecamatan Morosi, Kabupaten Konawe) - La Sampe; Irfan Ido; Jahidin Jahidin (Journal Publicuho, 2019)
This study aims to determine the public perception of the characteristics of foreign workers, that is a lifestyle, relationships and attitudes, by using estimator errors of 10%, a total of samples is 60 heads of families in Morosi village. The results of this study indicate that public perceptions of the lifestyle of foreign workers as much as 73.33% of respondents stated good, as many as 25.00% stated is less good, as much as 1.67% stated is not good. Public perceptions of the interaction of foreign workers as much as 53.33% of respondents stated is less good, as many as 36.67% stated is good, as many as 8.33% of respondents stated is not good, as much as 1.67% of respondents stated is very good. Public perceptions of the attitude of foreign workers as much as 53.33% of respondents stated is less good and as many as 46.67% of respondents stated is good.